On the Optimal Structure of Local Governments - Hochman, Oded; Pines, David; Thisse, Jacques-François (American Economic Review, 1995)
We show that space matters in designing the optimal provision of local public goods (LPG's). Geography imposes a particular institutional structure of local governments due to the overlapping of market areas associated with different LPG's. The optimum can be decentralized through local governments that have jurisdiction over market areas of all LPG types. This implies that the appropriate suppliers of LPG's are metropolitan governments which finance them through user charges and land rent. In addition, our approach invalidates the prevailing theory of fiscal federalism, according to which a layer of government should be established for each type of LPG.